SISTEM INFORMASI AKUNTANSI ANALISIS BIAYA PEMASARAN PT WSI KENDAL MENGGUNAKAN METODE TIME SERIES - Ahmad Ashifuddin Aqham; Bagus Sudirman; Indra Ava Dianta; Haris Ihsanil Huda; Selli Selfiyanti (Informatika: Jurnal Teknik Informatika dan Multimedia, 2024)
The marketing budget planning information system at PT WSI has not been equipped with a marketing budget planning system. In the absence of a marketing budget planning system, it is difficult to input future data and the number of revenue targets that have been achieved. The author hopes that the Marketing Cost Analysis Accounting Information System can make it easier for owners to make decisions, especially for more regular data management which will affect the company's finances for the better and can determine and know the amount of the budget plan and revenue that has been achieved in a certain period.